Activation of β2-Adrenoceptor Attenuates Sepsis-Induced Hippocampus-Dependent Cognitive Impairments by Reversing Neuroinflammation and Synaptic Abnormalities - Zong, Man-Man; Zhou, Zhi-Qiang; Ji, Mu-Huo; Jia, Min; Tang, Hui; Yang, Jian-Jun (Frontiers in Cellular Neuroscience, 2019)
Sepsis-associated encephalopathy induces cognitive dysfunction via mechanisms that commonly involve neuroinflammation and synaptic plasticity impairment of the hippocampus. The β2–adrenoceptor (β2–AR) is a G–protein coupled receptor that regulates immune response and synaptic plasticity, whereas its dysfunction has been implicated in various neurodegenerative diseases. Thus, we hypothesized abnormal β2–AR signaling is involved in sepsis–induced cognitive impairment. In the present study, C57BL/6 mice were subjected to cecal ligation and puncture (CLP) to mimic the clinical human sepsis-associated encephalopathy. The levels of hippocampal β2–AR, proinflammatory cytokines tumor necrosis factor (TNF–α), interleukin–1β (IL–1β), IL–6, cAMP–response element binding protein (CREB), brain derived neurotrophic factor (BDNF), post–synaptic density protein 95 (PSD95), and NMDA receptor 2 B subtypes (GluN2B) were determined at 6 h, 12 h, 24 h, 7 d, and 16 d after CLP. For the interventional study, mice were treated with β2–AR agonist clenbuterol in two ways: early treatment (immediately following CLP) and delayed treatment (on the eighth day following CLP). Neurobehavioral performances were assessed by open field and fear conditioning tests. Here, we found that hippocampal β2–AR expression was significantly decreased starting from 12 h and persisted until 16 d following CLP. Besides, sepsis mice also exhibited increasing neuroinflammation, down-regulated CREB/BDNF, decreasing PSD95 and GluN2B expression, and displayed hippocampus–dependent cognitive impairments. Notably, early clenbuterol treatment alleviated sepsis–induced cognitive deficits by polarizing microglia toward an anti–inflammatory phenotype, reducing proinflammatory cytokines including IL–1β, TNF–α , and up–regulating CREB/BDNF, PSD95 and GluN2B. Intriguingly, delayed clenbuterol treatment also improved cognitive impairments by normalization of hippocampal CREB/BDNF, PSD95 and GluN2B. In summary, our results support the beneficial effects of both early and delayed clenbuterol treatment, which suggests that activation of β2–AR has a translational value in sepsis–associated organ dysfunction including cognitive impairments.